A simple spectrophotometric method for the determination of tetracycline and doxycycline in pharmaceutical formulations using chloramine-T - Rufino, José L. [UNESP]; Fernandes, Flávio C.B. [UNESP]; Ruy, Mayara S. [UNESP]; Pezza, Helena R. [UNESP]; Pezza, Leonardo [UNESP] (Ecletica Quimica, 2010)
A simple, rapid, accurate and inexpensive spectrophotometric method for the determination of tetracycline and doxycycline has been developed. The method is based on the reaction between these drugs and chloramine-T in alkaline medium producing red color products with absorbance maximum at the ë = 535 and 525 nm for the tetracycline and doxycycline, respectively. The best conditions for the reactions have been found using multivariate method. Beer´s law is obeyed in a concentration ranges 1.03 x 10-5 to 3.61 x 10–4 mol L-1 and 1.75 x 10-5 to 3.48 x 10–4 mol L-1 for the tetracycline and doxycycline, respectively. The quantification limits were 5.63 x 10-6 mol L-1 and 7.12 x 10-7 mol L-1 for the tetracycline and doxycycline, respectively. The proposed method was successfully applied to the determination of these drugs in pharmaceutical formulations and the results obtained were in good agreement with those obtained by the comparative method at the 95% confidence level.
Keywords: Chloramine-T; Doxycycline; Spectrophotometric; Tetracycline